1981
DOI: 10.1128/jb.145.3.1299-1304.1981
|View full text |Cite
|
Sign up to set email alerts
|

Proton motive force across the membrane of Mycoplasma gallisepticum and its possible role in cell volume regulation

Abstract: A proton motive force (AjAH+) of 70 to 130 mV was measured across the membrane of Mycoplasma gallisepticum celLs. The membrane potential was measured by utilizing the lipid-soluble cation tetraphenylphosphonium. The method was validated by showing that in the presence of valinomycin the ratio of the concentrations (in/out) of tetraphenylphosphonium agreed well with those for K+ and Rb+. The pH gradient was calculated from the measured distribution ratio of benzoic acid. The proton motive force was approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Previous studies with M. gallisepticum (12,17) showed that the swelling of energy depleted cells was prevented by the addition of nondiffusable solutes such as sucrose or MgSO4 to the external medium. In the presence of glucose (with its associated high ATP level), no swelling occurs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with M. gallisepticum (12,17) showed that the swelling of energy depleted cells was prevented by the addition of nondiffusable solutes such as sucrose or MgSO4 to the external medium. In the presence of glucose (with its associated high ATP level), no swelling occurs.…”
mentioning
confidence: 99%
“…This is due to the inward diffusion of NaCl and water as a result of colloidosmotic and Donnan forces caused by intracellular nondiffusable macromolecules (11,14,22). The two bacteria without cell walls in which this phenomenon has been documented are Acholeplasma laidlawii (8) and Mycoplasma gallisepticum (12,17). Both species are known to be able to maintain their volume in the presence of glucose by an energy-dependent extrusion of NaCl and water from the cell.…”
mentioning
confidence: 99%
“…ApH and Aq~ were calculated as previously described [12] from the partition of radioactive markers between the intra-and extracellular water. For ApH, either 14C-labeled benzoic acid or 140 labeled methylamine were used, whereas for A+, [3H]-tetraphenylphosphonium (TPP +) plus unlabeled TPP + (8 #M) were utilized.…”
Section: Determination Of Intraeellular Volume Aph and A ~mentioning
confidence: 99%
“…At various time intervals, samples (20 ,ul each) were withdrawn, and the DNase I activity was terminated by adding 80 ,ul of A buffer containing 20 mM EDTA. The LUV-encapsulated plasmid was separated from the untrapped, digested plasmid by passing 100-,u samples through a Sephadex G-50 column in a 1-ml tuberculin syringe, as previously described (24). The amount of residual DNA in the LUV preparations was estimated by counting the radioactivity or determining total DNA and comparing with controls containing nonencapsulated plasmids.…”
mentioning
confidence: 99%
“…Samples, in duplicate, were layered onto the surface of 0.3 ml of silicone oil (550:556 grade; Dow Coming Corp.) in 1.5-ml plastic microcentrifuge tubes and centrifuged at 13,000 x g for 2 min. Under these conditions, the cells passed through the oil, forming a pellet at the bottom of the tube (24). The cell pellet was resuspended, and the amounts of residual radioactivity and fluorescence in the cells were determined.…”
mentioning
confidence: 99%